Abalones at risk: A global Red List assessment of Haliotis in a changing climate. - Howard Peters; Gina M Ralph; Laura Rogers-Bennett (PLoS ONE)
There is increasing awareness that marine invertebrates such as abalones are at risk from the combined stressors of fishing and climate change. Abalones are an important marine fishery resource and of cultural importance to Indigenous and non-Indigenous people. A highly priced marine delicacy, they are inherently vulnerable: individuals are slow-growing and long-lived and successful reproduction requires dense assemblages. However, their global conservation status is poorly understood. Using IUCN Red List methodology, we assessed the extinction risk to all 54 species of abalone (genus Haliotis). Of the 21 fished commercially for human consumption either now and/or in the past, 15 (71.43%) are classified as threatened, i.e., those identified as Critically Endangered, Endangered or Vulnerable. Of the 33 unexploited species, only five (15.15%) are so classified, making exploited species over four times more likely to face extinction, underscoring the impact of fishing on abalones already confronting a changing climate. The highest concentration of threatened species occurs along the North American Pacific coast. Here six of the seven species have been exploited, yet despite years of fishery closures with exemptions only in Alaska and Mexico, all are categorised as threatened. Climate driven stressors have led to mass mortalities, with competition from sea urchins and disease, aggravated by harmful algal blooms. In Australia the picture is mixed despite robust stock management, with some regions experiencing mass mortalities from marine heatwaves and viral spread. Poaching has reached its apogee in South Africa, where organised criminal gangs have reduced the legal fishery of Haliotis midae, 'perlemoen' almost to a footnote, accompanied by widespread recruitment failure. In response, the authorities have focused on abalone ranching and stock enhancement. In Japan, with a long history of abalone fishing, wild stocks are routinely supplemented with hatchery-bred juveniles. Collaboration between restoration aquaculture and fisheries, including sea urchin control and kelp restoration, offers hope for rebuilding stocks against a backdrop of escalating environmental stressors.